2006
DOI: 10.1074/jbc.m511037200
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal as a Signal Initiator for Activation of the Stress-activated Protein Kinase Cascade in the Fission Yeast Schizosaccharomyces pombe

Abstract: Methylglyoxal (MG) is Methylglyoxal (MG,2 CH 3 COCHO) is a typical 2-oxoaldehyde derived from glycolysis, a ubiquitous energy-generating system present in all types of organism; nevertheless, MG inhibits the growth of cells (1). For example, MG induces apoptosis in some mammalian cells by provoking production of reactive oxygen species (2). Actually, cells exhibiting MG-induced apoptosis, such as Jurkat cells and HL60 cells, are sensitive to reactive oxygen species (3, 4). On the other hand, MG induces necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 49 publications
(67 reference statements)
0
26
0
Order By: Relevance
“…We previously reported that MG causes acute cellular responses in yeasts (10,11). For example, the exogenous addition of MG activated yeast AP-1-like transcription factors (Yap1 in Saccharomyces cerevisiae and Pap1 in Schizosaccharomyces pombe) through the reversible modification of their critical Cys residues within 45 min (10,11). MG was also found to enhance the influx of extracellular Ca 2ϩ into the cell, thereby activating the Ca 2ϩ /calcineurin system in S. cerevisiae (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that MG causes acute cellular responses in yeasts (10,11). For example, the exogenous addition of MG activated yeast AP-1-like transcription factors (Yap1 in Saccharomyces cerevisiae and Pap1 in Schizosaccharomyces pombe) through the reversible modification of their critical Cys residues within 45 min (10,11). MG was also found to enhance the influx of extracellular Ca 2ϩ into the cell, thereby activating the Ca 2ϩ /calcineurin system in S. cerevisiae (12).…”
mentioning
confidence: 99%
“…The harmful effects of MG on cellular functions have been attributed to MG-derived AGEs (4)(5)(6)(7)(8)(9). We previously reported that MG causes acute cellular responses in yeasts (10,11). For example, the exogenous addition of MG activated yeast AP-1-like transcription factors (Yap1 in Saccharomyces cerevisiae and Pap1 in Schizosaccharomyces pombe) through the reversible modification of their critical Cys residues within 45 min (10,11).…”
mentioning
confidence: 99%
“…In Sc. pombe, the Sty1 pathway is activated in response to diverse stresses, such as osmotic stress, heat shock, oxidative stress, nitrogen limitation, carbon starvation, UV light, methylglyoxal, cold stress, arsenite and pressure (Degols et al, 1996;Degols & Russell, 1997;George et al, 2007;Millar et al, 1995;Rodríguez-Gabriel & Russell, 2005;Soto et al, 2002;Takatsume et al, 2006). In Candida (Ca.)…”
Section: Introductionmentioning
confidence: 99%
“…MG activates transcription factors such as Yap1 and Msn2, and triggers a Hog1 mitogen-activated protein (MAP) kinase cascade in Saccharomyces cerevisiae. Regarding the activation of Hog1 by MG, Sln1, an osmosensor possessing histidine kinase activity, functions as a sensor of MG (Maeta et al, 2005;Takatsume et al, 2006). Our understanding of the signaling role of MG in higher plants is at a rudimentary stage.…”
Section: Methylglyoxal As An Initiator Of Activation Of Signal Transdmentioning
confidence: 99%
“…However, a major gap exists in our understanding about how plants sense MG and oxidative stress in different subcellular compartments and how this stress signal is transduced, thus activating largescale and coordinated expression of different enzymes and metabolites of their detoxification pathways. A complete understanding of the interaction between ROS, MG and plant hormones and transcription factors (Sasaki-Sekimoto et al, 2005;Takatsume et al, 2006) and components of ROS and MG detoxification pathways in different subcellular www.intechopen.com Glyoxalase System and Reactive Oxygen Species Detoxification System in Plant Abiotic Stress Response and Tolerance: An Intimate Relationship 257 compartments will reveal more subtle regulatory roles of both detoxification systems in abiotic stress tolerance. In addition, identification of master regulators that control stress response activation will accelerate the process to improve and strengthen plant fitness to changing climates.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%